Integrating Disability, Transforming Feminist Theory - Garland-Thomson, Rosemarie (NWSA Journal, 2002)
This essay aims to amplify feminist theory by articulating and fostering feminist disability theory. It names feminist disability studies as an academic field of inquiry, describes work that is already underway, calls for needed study and sets an agenda for future work in feminist disability studies. Feminist disability theory augments the terms and confronts the limits of the ways we understand human diversity, the materiality of the body, multiculturalism, and the social formations that interpret bodily differences. The essay asserts that integrating disability as a category of analysis and a system of representation deepens, expands, and challenges feminist theory. To elaborate on these premises, the essay discusses four fundamental and interpenetrating domains of feminist theory: representation, the body, identity, and activism, suggesting some critical inquiries that considering disability can generate within these theoretical arenas.
Keywords: EDI; activisme; approches et analyses; corps; cours; discipline; militance; premier cycle; queer; ressource en ligne; santé; sciences humaines; sciences sociales; sex1920; thématiques; études critiques du handicap; études féministes

The fourth world: an indigenous perspective on feminism and aboriginal women's activism - Ouellette, Grace Josephine Mildred Wuttunee (Basics from Fernwood Publishing, 2002)
"This book is not about feminism. Rather, feminism is the basis of the discussion, an example of how understanding oppression must consider a number of barriers. Euro-Canadian feminists rarely address the circumstances that are unique to First Nations' women, instead working with the assumption that all women are a part of a similar struggle. Ouellette attempts to confront these barriers. Throughout interviews with a number of women, she highlights the following four questions. To what extent do Aboriginal women understand experience and articulate their oppression? To what extent do colonized women perceive racism as the source of their oppression? To what extent do Aboriginal women view male domination within their own Aboriginal societies as the source of the oppression? How do Aboriginal women articulate racism and gender oppression?The author argues that there will always be a dichotomy between European and Aboriginal thought. This book makes an important contribution toward a greater understanding of Aboriginal thought and an Aboriginal perspective on society. The Fourth World theory is an integrate part of the "Circle of Life" philosophy of Aboriginal people. In keeping with oral traditions, these teachings are passed on at gatherings and in private conversations. They compromise a distinctly Aboriginal worldview."
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs -- qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those -- the vast majority -- who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe